Stretch-Elicited Autocrine/Paracrine Mechanism in the Heart - Cingolani, Horacio Eugenio (2003)
An autocrine/paracrine mechanism is triggered by stretching the myocardium. This mechanism involves the release of angiotensin II (Ang II), the release/increased formation of endothelin (ET), the activation of the Na+/H+ exchanger (NHE), the increase in intracellular Na+ concentration ([Na+]i), and the increase in the Ca2+ transient that underlies the so called slow force response (SFR) to stretch. This autocrine/paracrine mechanism could explain how a change in afterload alters cardiac contractility as was reported by Anrep in 1912.